The Highway as a Social Stage: Virtual Ethnography of Motorcycle Rider Behavior in Social Media Content - Bakharuddin Muhammad Syah; Rendy Ananta Prasetya (Journal of Innovative and Creativity (Joecy), 2026)
This study examines how the cultural values of “speed,” “challenge,” and “solidarity” are narrated through social media content depicting the traffic behavior of motorcycle riders in Indonesia. Using a qualitative approach with netnography (Kozinets, 2015) and visual discourse analysis (Rose, 2016), this research analyzes uploaded accident videos, “street racing” actions, and netizen comment sections from Instagram, TikTok, and YouTube (January 2024 – March 2026), as well as official police content (@divisihumaspolri, @korlantaspolri). Data were analyzed using symbolic interactionism (Goffman, 1963, 1967), social network theory (Castells, 2009), and visual/digital anthropology (Pink, 2021). The results show three main findings. First, the value of “speed” functions as a symbol of social status, masculinity, and freedom, displayed through rolling, extreme cornering, and illegal racing actions, and is associated with specific motorcycle brands as identity markers. Second, the value of “challenge” is represented as a risk performance deliberately recorded for public consumption, where social validation mechanisms (likes, comments, shares, hashtags #fyp) encourage increasingly risky behavior while simultaneously creating public pressure that punishes dangerous actions. Third, the value of “solidarity” manifests in bonds of togetherness in convoys and post‑accident support (prayers, donations, visits). This study also finds that traffic police appear in these narratives in three overlapping roles: as law enforcers, as targets of public criticism, and as part of the social performance itself. This study concludes that in the digital era, the highway has transformed into a social stage where motorcycle riders not only travel but also perform, are judged, and are remembered by the online public. Recommendations include the need for more dialogic and culturally sensitive police communication strategies, involvement of motorcycle communities in safety campaigns, and moderation of risky content by social media platforms.